Preparation of graphene-based novel high-performance electrode materials and its applications in supercapacitors - Ong, Jackson Jin Jie (2015)
Due to the limited fossil fuel and the rapidly increasing demand in terms of energy, sourcing for alternative energy storage has been one of the critical challenges. Supercapacitors have been one of the popular choices, and have also become an essential theme in recent scientific studies and research. In this work, a new method was used to prepare the 3D nickel foam/graphite film/CNTs/Ni(OH)2 architecture, which will be used as the electrode materials for supercapacitors. With a high capacitance of 976.7 Fg-1 at a current density of 1 Ag-1 and good cycling stability, the 3D nickel foam/graphene/CNT/Ni(OH)2 composite gives promising results to be used as electrode for supercapacitors. This was made possible due to the presence of the graphene layer on the nickel foam, which can boost charge/discharge process. By using 3D nanoarchitectured electrodes, there will be more ion absorption sites for double layer formation due to larger surface area and a bigger electrode/electrolyte contact area per unit mass, resulting in a higher charge-transfer reactions. The results of this project has provided an alternative method to improve the rate capability and cycling stability, and thus a promising application in supercapacitors.